Geochemical behavior of lateral peat degradation in the Kubu Raya Region, West Kalimantan, Indonesia - Ivansyah, Okto; Zubair, Hazairin; Irfan, Ulva Ria; Widodo, Sri (Brawijaya University, 2025)
This study investigated the lateral distribution of geochemical parameters in peatlands within the Punggur Besar River–Kapuas River Peat Hydrology Unit (KHG) in Kubu Raya District, West Kalimantan Province, Indonesia. Peatland degradation in this area is primarily caused by land clearing, uncontrolled drainage, and forest fires, which adversely impact the soil's physical and chemical properties. Key geochemical parameters analyzed include nitrogen (N), phosphorus (P), potassium (K), pH, organic carbon, and cation exchange capacity (CEC). Spatial distribution was mapped using GIS technology. The results showed significant variation in nutrient content and soil pH across the study area. Nitrogen content varied between 0.1% and 1.6%, indicating areas of high and low vegetation productivity. Low phosphorus levels in most regions suggest nutrient deficiencies, while potassium concentrations exhibit variability, indicating a potential need for fertilization. Predominantly acidic soil pH (2.8-6.3) challenges vegetation growth and increases fire risk. These discoveries contribute to a fundamental understanding of the geochemical dynamics of peatlands, indispensable for leading sustainable management and restoration efforts. By recognizing areas of high fertility and those requiring restoration interventions, this research assists effective land-use planning and climate mitigation strategies in degraded peatland ecosystems.